The Influence of Artificial Intelligence Utilization on School Financial Decision-Making Effectiveness - Sri Rahayu; Ken Sabardiman Soetjipto (Jurnal Info Sains : Informatika dan Sains, 2026)
This study aims to examine the influence of Artificial Intelligence (AI) utilization on the effectiveness of school financial decision-making at SMK Bina Mandiri. This research employed a quantitative associative approach involving 30 teachers as respondents, selected through a saturated sampling technique. Data were collected using a Likert-scale questionnaire and analyzed through validity testing, reliability testing, classical assumption testing, linear regression analysis, t-test, F-test, and the coefficient of determination (R²) using SPSS. The results indicate that all statement items were valid and reliable, the residual data were normally distributed, and no heteroscedasticity was found. The regression equation obtained was Y = 6.892 + 0.784X, indicating that AI utilization has a positive effect on financial decision-making effectiveness. The t-test result (t-count 5.921 > t-table 2.048, sig. 0.000) confirms that H1 is accepted, while the F-test result (F-count 35.058 > F-table 4.196, sig. 0.000) confirms that the regression model is fit for use. The coefficient of determination (R²) of 0.556 indicates that 55.6% of the variance in financial decision-making effectiveness is explained by AI utilization, while the remaining 44.4% is explained by other factors outside this research model. This study recommends that schools enhance AI training and literacy for teachers and staff involved in school financial management.